Strategi Inovatif dalam Mengembangkan Pendidikan Inklusif: Pelatihan Peran Guru, Fasilitas Memadai, dan Kolaborasi Efektif - Debora Siregar; Audrey Sabrina; Elsa Septaria Sihotang; Siti Khadijah; Sonia Manihuruk; Anggia Puteri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Inclusive education aims to provide equal learning opportunities for all learners, including those with special needs. However, its implementation in Indonesia still faces various challenges, such as educators' readiness, limited facilities and lack of cooperation between schools, parents and communities. This study aims to identify innovative strategies in developing inclusive education so that it can be effectively implemented in the school environment. This research uses a descriptive qualitative method with a literature study approach. Data sources came from various books, scientific journals and publications relevant to inclusive education. Data collection techniques were conducted through literature review, while data analysis techniques used critical analysis to identify patterns, challenges and solutions in the implementation of inclusive education. The results show that intensive and practice-based teacher training, providing adequate infrastructure and strengthening collaboration between parties play an important role in creating a more inclusive learning environment. Therefore, clear policies, continuous training and facility support are needed to realize a fair and equal education system